Exercise induced muscle damage & repair - Sullivan, M.
Serial repetitions of maximal effort eccentric actions cause characteristic changes in correlates of muscle damage (7). Peak soreness is experienced 2-3 days post exercise while peak swelling occurs about 5 days post exercise. Maximal strength and the ability to fully flex the arm show the greatest decrements immediately following exercise and then there is a linear restoration over the next 10 days (7). Blood levels of CK do not increase precipitously until 2 days after the exercise, which is also the time when spontaneous muscle shortening is most pronounced. Whether the similarity in the time courses of some of these responses implies that they are caused by similar factors remains to be determined (7). According to Clarkson et al. (7), performance of one bout of eccentric exercise produces an adaptation such that the muscle is more resistant to damage from a subsequent bout of exercise. The length of the adaptation differed among the measures such that when the exercise regimens are separated by 6 weeks, all measures show a reduction in response on the second, compared with the first bout (7). However, after 10 weeks only CK and spontaneous muscle shortening show a reduction in response (7). Furthermore, after 6 months there is a reduction only in the CK response (7). A combination of cellular factors and neurological factors seems to be involved in the adaptation response (7). There have been studies concerning the effects of training on exercised induced muscle damage. In one study by Balnave and Thompson (4), they found that training reduces the extent of muscle function impairment, however, they also found no long-lasting repeated bout adaptation. Furthermore, in a recent study by Jakeman and Maxwell (12), they investigated the effects of antioxidant vitamin supplementation upon muscle contractile function following eccentric exercise. It was concluded that prior supplementation of vitamin C may exert a protective effect against exercise induced muscle damage. However, they believe more research needs to be done to obtain conclusive results. So it appears that no real protection against exercised induced muscle damage exists.